Relativity of Information Presented in Statistical Reports Prepared by Public Hospitals In Poland - Szewieczek , Aleksandra; Strojek-Filus, Marzena (Studia Oeconomica Posnaniensia, 2016)
The set of reports prepared by health care entities is extensive. Many of these reports are presented for statistics goals. There are financial, non-financial and mixed reports. The article presents the scope of the whole reporting system in health care entities in Poland, with particular focus on its statistical character. The study reports some areas of statistical reports which tend to be presented in many different ways, which may result in a different view of financial position of a health care system’s elements. Simultaneously, the complexity of the statistical reporting system in public health care services is presented.